Alternative induced molting methods for feed withdrawal and their effect on post molt egg quality parameters of White Leghorn hens - AGARWAL, R; KHILLARE, G S; SAXENA, R; SASTRY, K V H; TRIPATHI, V; SINGH, R P; MOHAN, JAG (The Indian Journal of Animal Sciences, 2018)
Forced molting were practiced using the flock of hens by promoting a second laying cycle. In the present study, the effectiveness of induced molting method was studied in comparison to conventional feed withdrawal in terms of egg quality parameters. Layer chicken (160), 72–week-old were divided into 4 groups and were subjected to induce molting for a period of 14 days. The first group that received ad lib. water with complete feed withdrawal served as a control. The birds of the second group received ad lib. layer ration without calcium fortified with organic zinc (20,000 ppm) along with organic copper (600 ppm/kg of feed). The third group was provided with organic zinc (20,000 ppm) along with organic cobalt (150 ppm/kg of feed). The fourth group was provided with organic zinc (20,000 ppm) with organic chromium (500 ppm/kg of feed). Egg and shell weight were significantly different among different treatments; whereas, in shell thickness, egg production and body weight reduction, no significant difference was observed. The feed withdrawal treatment resulted in lower egg weight than other treatments. In conclusion, mineral supplemented methods could be substituted for conventional feed withdrawal method of induced molting.